Deciphering the Thermal Failure Mechanism of Anode‐Free Lithium Metal Pouch Batteries - Zhang, Xiaohu; Huang, Lang; Xie, Bin; Zhang, Shenghang; Jiang, Zhaoxuan; Xu, Gaojie; Li, Jiedong; Cui, Guanglei (Advanced energy materials, 2023)
Anode‐free lithium metal batteries (AFLMBs) are the subject of increasing attention due to their ultrahigh energy density, simplified structure, reduced cost, and relatively high safety, but their thermal runaway performance under abuse conditions has been rarely explored, and a clear understanding of whether the absence of a highly‐reactive lithium metal anode is equal to thermal runaway free remains elusive. Herein, by systematically examining the thermal runaway characteristics of a 2.0 Ah AFLMB, it is revealed that under elevated temperatures, discharged anode‐free pouch cell is safe while the fully‐charged one indeed undergoes thermal runaway, but with a milder intensity than that of a lithium metal battery with the same capacity. Moreover, mechanistic investigations demonstrate that thermal runaway of an AFLMB employing a conventional electrolyte is triggered and dominated by anode‐induced exothermic interactions and the broken separator induced electrodes interaction. Moreover, it is shown for the first time that adding fluoroethylene carbonate in an electrolyte leads to ring‐opening repolymerization at 170 °C to form a thermal‐stable solid layer between anode and cathode, which inhibits the direct contact of electrodes and effectively postpones violent self‐heating. This comprehensive exploration of thermal runaway characteristics and mechanisms of large format AFLMBs sheds fresh light on developing high energy density and safety‐enhanced lithium metal batteries. Fully charged anode‐free lithium metal batteries undergo thermal runaway triggered by anode‐induced interactions in thermal abused conditions. It is shown that at high temperatures, fluoroethylene carbonate in electrolyte undergo re‐polymerization with lithium salts and form a thermally stable coating layer attached to the cathode, inhibiting the direct contact of anode and cathode and consequently improving the thermal safety of the pouch cell battery.